2016
DOI: 10.3109/02699052.2016.1146799
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing community case management and care hours for clients with traumatic brain injury living in the UK

Abstract: Objective: To investigate the relationship between deficits associated with traumatic brain injury (TBI) and case management (CM) and care/support (CS) in two UK community samples. Research design: Prospective descriptive study. Method: Case managers across the UK and from a single UK CM service contributed client profiles to two data sets (Groups 1 and 2, respectively). Data were entered on demographics, injury severity, functional skills, functional-cognition (including executive functions), behaviour and CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The application of a structured bathing and dressing retraining program resulted in independence after only 11 days of treatment (32). Conversely, based on our findings, we hypothesize that, if after sufficient training, a client is unable to manage the problem-solving required for independence in an IADL task, it is unlikely that the client will be able to learn to perform tasks that have greater problem-solving demands (20). What seems to be required is to reduce the onthe-spot decision-making requirements so the task becomes invariant.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…The application of a structured bathing and dressing retraining program resulted in independence after only 11 days of treatment (32). Conversely, based on our findings, we hypothesize that, if after sufficient training, a client is unable to manage the problem-solving required for independence in an IADL task, it is unlikely that the client will be able to learn to perform tasks that have greater problem-solving demands (20). What seems to be required is to reduce the onthe-spot decision-making requirements so the task becomes invariant.…”
Section: Discussionmentioning
confidence: 76%
“…It has been proposed that adequate IADL performance post TBI depends on both the individual's cognitive status and their self-awareness (18,19). In a prior publication we reported that lack of insight was associated with increased need for case management and care-support for individuals living in the community following TBI (20). To our knowledge, there have been no studies that have examined how insight relates directly to ADL versus IADL performance after TBI (18).…”
Section: Traumatic Brain Injury; Brain Injury; Activities Of Daily LImentioning
confidence: 94%
See 3 more Smart Citations